Darwin Koenig letter to Thomas H. Kent regarding winter bird sightings, March 4, 1983 - Koenig, Darwinet al (1983)
Letter from Darwin Koenig to Thomas H. Kent regarding winter bird sightings, March 4, 1983. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1982-1983. Epson - sheet feed